Kodyfikacja a progresywny rozwój prawa międzynarodowego publicznego - Szuniewicz, Marta (Kwartalnik Prawa Publicznego, 2013)
In context of variety of customary and conventional norm of international law their systematization and explanation seemed necessary. According to above relevant actions were taken in order to collect and set in order existing norms of international law (codification of international law) and to formulate new norms in that branch of law (progressive development of international law). The codification work of the UN International Law Commission encompasses international treaties and scientific restatement. Whereas first method brings problems with their universal recognition, the second one deals with difficulties in authoritative identification of customary international law norms. The precise separation of codification and progressive development of international law appeared impossible in practice at the stages of topics selection, procedures and final effects. The process of writing down binding norms of international law requires some modifications aim at removing inconsistences, explaining certain questions or adopting to changing conditions of international relations. Those are the features of the progressive development. The codification efforts may be recognized as a method of progressive development of international law, whereas aspect of development is engaged in process of codification of international law. Both normative categories should be therefore seen as elements improving the regime of public international law.